Effects of hydrochlorothiazide on contraction and 86Rb efflux in rat aorta - Wang Gui-Song; Li Yun-Shan; Fu Shao-Xuan (Acta Pharmacologica Sinica, 2016)
Hydrochlorothiazide (HCT) (0.1, 0.3 mmol.L-1) inhibited the contraction of rat aortic strips induced by low (< 40 mmol.L-1), not higher concentrations of KCl. HCT (0.3 mmol.L-1) did not inhibit the CaCl2-induced contraction of the aortic strips depolarized with high K+ (KCl 80 mmol.L-1). The inhibitory effect of HCT (0.1 mmol.L-1) on KCl (20 mmol.L-1)-induced contraction was markedly antagonized by BaCl2 (0.1 mmol.L-1) and tetraethylammonium (TEA) (0.3 mmol.L-1), but not by glibenclamide (Gli, 0.01 mmol.L-1). With norepinephrine (NE) or 5-HT as agonists, HCT (0.3 mmol.L-1) also inhibited the contractions of rat aortic strips. In the 2 components of NE-induced contraction, HCT inhibited only the tonic component depending on Ca2+ influx, but not the phasic component elicited by the release of intracellular Ca2+. The inhibitory action of HCT was endothelium-independent. That the HCT (3 mmol.L-1) increased the 86Rb efflux rate coefficient was antagonized by BaCl2 (0.1 mmol.L-1), but not by Gli (0.01 mmol.L-1). The results indicated that the inhibitory effect of HCT on the contraction of rat aorta was attributable to the opening of membrane potassium channels.